2018
DOI: 10.1128/jvi.00110-18
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Vaccine Expressing Consensus Hemagglutinin-Esterase Fusion Protein Protected Guinea Pigs from Infection by Two Lineages of Influenza D Virus

Abstract: Two lineages of influenza D virus (IDV) have been found to infect cattle and promote bovine respiratory disease complex, one of the most commonly diagnosed causes of morbidity and mortality within the cattle industry. Furthermore, IDV can infect other economically important domestic livestock, including pigs, and has the potential to infect humans, which necessitates the need for an efficacious vaccine. In this study, we designed a DNA vaccine expressing consensus hemagglutinin-esterase fusion (HEF) protein (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The study showed that the vaccinated animals showed significant titers of neutralizing antibodies against both lineages of IDV and were protected against the intranasal IDV challenge. Although studies in past have shown the potential of DNA vaccines against IAV [81], this study is claimed to be the first to show the effect of a DNA vaccine against IDV and thus a promising approach to manage infections [82].…”
Section: Strategies To Control Idv Infection and Management Of Futmentioning
confidence: 99%
“…The study showed that the vaccinated animals showed significant titers of neutralizing antibodies against both lineages of IDV and were protected against the intranasal IDV challenge. Although studies in past have shown the potential of DNA vaccines against IAV [81], this study is claimed to be the first to show the effect of a DNA vaccine against IDV and thus a promising approach to manage infections [82].…”
Section: Strategies To Control Idv Infection and Management Of Futmentioning
confidence: 99%
“…However, the protective effects of these vaccines are unsatisfactory in some cases of respiratory illness, suggesting that the cases may be associated with flu D virus infection. Therefore, vaccine development for flu D should be considered [ 9 , 23 ]. The antigenic heterogeneity among all flu D virus HEFs shown in this study emphasizes that, when developing flu D vaccine in Japan, the D/Japan-lineage virus should be used as a seed virus to yield maximal vaccine efficacy.…”
mentioning
confidence: 99%
“…We designed consensus optimized DNA vaccines targeting the oncogenic EBV latent proteins commonly seen in malignancies, which are EBNA1, LMP1, and LMP2A. Consensus immunogens can focus the immune response towards conserved regions of important antigens, allowing for increased T cell cross reactivity as well as partially compensating for minor variability in the vaccine targeted antigens [48,49,50]. Consensus sequences using GD1 (type 1), B95-8 (type 1), and AG876 (type 2) EBV genes were generated for all 3 antigens (Figure 1A) to optimize the ability of the vaccines to elicit immune responses against all common viral strains, which are phylogenetically similar [51].…”
Section: Resultsmentioning
confidence: 99%